Meningoencephalitis of Unknown Origin in Dogs - Garcia , Cinthia; Schallenberger da Silva, Rúbia; Davi dos Santos , Ezequiel; Machado Costa , Márcio; Dalla Palma, Mariana; Costa da Motta, Adriana; Policarpo Machado , Tanise; Helena de Alcantara Barcellos, Heloisa (Acta Scientiae Veterinariae, 2023)
Background: Meningoencephalitis of unknown origin (MUO) is a critical cause of neurological disorders in dogs, mainly affecting small young individuals. Its symptomatology is varied and depends on the affected neuroanatomic region. The ante mortem diagnosis of this condition is uncertain, being achieved by discarding other conditions and often occurring definitively only by performing a necropsy. Thus, this study aims to report 2 cases of meningoencephalitis, one necrotizing and the other granulomatous in dogs. Cases: Case 1. A 3-year-old, Shih Tzu bitch with a body weight of 4 kg, showing proprioceptive ataxia, behavior of walking in circles, and evolving rapidly to non-ambulatory paresis, was treated. The neurological examination showed a posture of decerebrate stiffness and absence of withdrawal reflex and proprioception, suggesting brainstem injury. Laboratory tests showed mild neutrophilia and lymphopenia, while the rapid test for distemper was non-reactive. The cerebrospinal fluid (CSF) analysis showed lymphocytic pleocytosis, and the PCR tests of the CSF, blood, and urine for the detection of infectious diseases were negative, as well as the culture. With no improvement in clinical condition and exams showing a progressive degenerative condition unresponsive to available treatments, the tutor opted for euthanasia of the patient. The subsequently requested necropsy confirmed the diagnosis of granulomatous meningoencephalitis. Case 2. This case refers to a 1-year-and-5-month-old male Maltese breed weighing 4.8 kg. This animal presented walking in circles behavior and loss of vision for a week, with signs worsening rapidly. In the neurological evaluation, the patient presented sensitivity in the middle ear, difficulty opening the mouth, hearing deficit in the right ear, blindness in the right eye, a proprioceptive deficit in the right anterior limb, and head pressing. Laboratory tests showed nonregenerative anemia and mild lymphopenia. After 1 day of hospitalization, the patient showed worsening clinical condition, with obstruction, absence of facial and auricular sensitivity, and nasal stimulus. In addition, onset of generalized seizures was observed; therefore, CSF was analyzed, which did not present significant alterations except for detecting reactive lymphocytes. The bacteriological culture of CSF resulted in no bacterial growth. In addition, the same neurological PCR panel performed for the previous patient was negative. After 5 days of intensive care, the patient presented a cardiorespiratory arrest and died. The subsequently requested necropsy confirmed the diagnosis of necrotizing meningoencephalitis. Discussion: The 2 reported cases confirm that MUO should be considered during the differential diagnoses of patients with neurological alterations. It is known that small-breed dogs are predisposed to these diseases. Laboratory tests and medical imaging are crucial for clinical guidance, helping to discard other neurological pathologies, especially those due to bacterial, fungal, and/or viral agents. However, definitive diagnosis of MUO can only be performed through necropsy and histopathological analysis. For the reported cases, CSF analysis, neurological PCR panel for detecting possible infectious agents, and bacterial culture were essential to rule out other possible causes of meningoencephalitis. Unfortunately, MUO includes progressive neurological disorders causing the patient’s death. Keywords: meninges, necropsy, histopathology, diagnosis.